2020
DOI: 10.1108/intr-06-2019-0256
|View full text |Cite
|
Sign up to set email alerts
|

Online service or virtual community? Building platform loyalty in reward-based crowdfunding

Abstract: PurposeThis study examines how individual contributors' evaluation of the two aspects in reward-based crowdfunding—service and community—influences the formation of platform loyalty. It also seeks to determine the conditions under which the evaluation is positive.Design/methodology/approachWe collaborated for data collection with two reward-based crowdfunding platforms in South Korea that primarily promote crowdfunding campaigns in the creative domains. We combined the survey data collected from 578 contributo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 102 publications
0
18
0
Order By: Relevance
“…The observed publications use crowdfunding not solely for raising monetary funds, but also for generating feedback and new ideas, as well as for triggering a marketing effect in terms of awareness and reach generation [31,32,104]. Moreover, the observed organizations tend to build up communities by applying crowdfunding techniques, which serve them as a starting point when launching new follow-up campaigns [167,168]. The use of external agencies to assist during crowdfunding campaigns, as outlined by Behl et al [111] and Du et al [112], could not be observed in the sample.…”
Section: Resultsmentioning
confidence: 99%
“…The observed publications use crowdfunding not solely for raising monetary funds, but also for generating feedback and new ideas, as well as for triggering a marketing effect in terms of awareness and reach generation [31,32,104]. Moreover, the observed organizations tend to build up communities by applying crowdfunding techniques, which serve them as a starting point when launching new follow-up campaigns [167,168]. The use of external agencies to assist during crowdfunding campaigns, as outlined by Behl et al [111] and Du et al [112], could not be observed in the sample.…”
Section: Resultsmentioning
confidence: 99%
“…self-image congruence, brand-image congruence and value congruence) to measure perceived fit sub-dimensions; all the scales were from peer-reviewed articles regarding the virtual brand community. Self-image congruence measures the relatedness between the brand's and the consumer's self-image, using three items from Ryu and Suh (2020); brand image congruence measures the degree to which the social cause is congruent with the brand's image, using three items adapted from Song and Kim (2020); value congruence measures the extent to which the core values of the social cause are congruent with the consumer's values, using three items adapted from (Ye et al , 2021). Community identification was measured using five items from Wang et al (2021).…”
Section: Methodsmentioning
confidence: 99%
“…Self-image congruence is consumer-relationship-focused congruence because it depicts individuals as similar to the image of a given entity, such as a brand, product, or organization (Sirgy et al , 1997). Consumers are more inclined to purchase products that are consistent with their self-image to realize image congruence, which drives loyalty toward the brand's virtual community (Ryu and Suh, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ryu and Suh thought that users’ attitudes towards the service provided by the community and their sense of belonging to the community were two key factors affecting their loyalty. 27 According to the exploration of Koh and Kim on the impact of knowledge-sharing behavior on virtual community loyalty from the perspective of e-business, the loyalty of users to the community can be formed by their sense of community, driven by knowledge-sharing behavior in the virtual community. 28 Virtual community loyalty in this study refers to the willingness of users to repeatedly browse the website and recommend it to others, including attitudinal and behavioral loyalty to the virtual community.…”
Section: Literature Reviewmentioning
confidence: 99%